THE EFFECTS OF DRIBBLING AND LEG LENGTH EXERCISE ON DRIBBLING ABILITY IN THE SPORTS OF SSB PORMA KUDUS - Elmando, Welly; Nasuka, Nasuka; Sulaiman, Sulaiman (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
This study aims to analyze the basic techniques of dribbling, and leg length in the early childhood development program of SSB Porma in Kudus Regency. This research uses a quantitative approach with the two-way ANOVA model. The subjects in this study were SSB Porma Kudus athletes in Kudus Regency. The results of this study are the results of the calculation of leg length variables are obtained tvalue = 0.000 < ttable = 0.050, the results of the calculation of the type of exercise variable are obtained tvalue = 0.019 < ttable = 0.050, in the type of exercise variable, the length of the leg are obtained tvalue = 0.940 > ttable = 0.050. The conclusion of this research is there is a difference in the level of dribbling speed between respondents with the slalom drill dribbling training method and respondents who are given the t-drill dribbling training method, and there is a difference in the level of dribbling speed between respondents with long limbs and respondents with low limbs, there is no interaction between dribbling training methods with leg length categories in influencing dribbling speed. Research suggestions are players should increase in dribbling slalom drill practice rather than dribbling t-drill, the trainer should provide various forms of dribbling exercises, it is better to have complete facilities and infrastructure with the aim of supporting the training.